Fundraising Strategy In Increasing Zis Fund Acceptance At Amil Institutions (Lazwashal) - Erlangga Hakim Manurung; Siti Aisyah (CV Putra Publisher, 2023)
Basically related to the explanation that the concept of fundraising is very important to efforts to improve the management of the fund ZIS (Zakat,Infaq, and Sodaqoh) as well As the management of the fund waqof. Not only itusaja the process of Fundraising can also be defined as the process of collecting funds or fund raising. Which in this case can be used to finance the program operations of an institution that ultimately aims to achieve the mission and vision of the institution. In this case it is necessary needed a strategy or direction of an approach in the process of raising funds in order to obtain the maximum results possible. Fundraising is related to the ability of individuals, organizations, and institutions of law where for invites and used effects other people, which can cause awareness of the sera sense of concern that exist in each. Can also be used to manage the fund waqof on the concept of fundraising this. There are several strategies fundraising that need to be considered, among others : analyzing opportunities, strategize fundraising, plan a program of collecting, organizing, implementing, controlling the efforts of the collection of zakat. Things like this berpengruh great on the course of zakat in every Institution including LAZWASHAL